THE PUBLIC TRUST IMPACT OF VIOLATIONS OF ETHICAL CODES IN CONSTITUTIONAL COURT DECISIONS - Adinda Isya Handy Putri; Balqis Vaniia Gitta; Emmanuella Patricia Sinaga; Irene Gianti Citra Nadia Moho; Nila Akmala (Problematika Hukum, 2020)
This research explores the impacts resulting from severe breaches of ethical codes in the decisions of the Constitutional Court that have led to a drastic decline in public trust. This decline is considered a significant barrier to the progress and sustainability of Indonesia’s constitution in the future. These impacts not only affect the constitutional system but also permeate specific elements within society. It is a serious issue that can damage the integrity of the Constitutional Court, an institution that should uphold honesty and transparency in carrying out its duties and authorities. The Constitutional Court, which should be a fully trustworthy institution, is now perceived to have tarnished its image. Various new perspectives have emerged, measuring the breakdown of integrity within the Constitutional Court. The diminishing trust of the public signifies a wavering authority and independence of this institution. There have been numerous actions by the public showing signs of disappointment and regret towards the Constitutional Court. This calls for a comprehensive evaluation to eradicate the roots that have damaged the core of this institution. Such efforts need to be undertaken by all layers of society, accompanied by contributions and sacrifices, to safeguard and oversee that our constitution remains unharmed and leads to a better and sustainable constitutional future.Keywords: Constitutional Court, Severe Breaches, Drastic Decline